Changing fortunes income mobility and poverty dynamics in Britain - Jenkins, Stephen P. (Oxford : Oxford University Press, 2011)
This book documents the patterns of income mobility and poverty dynamics in Britain and how they have changed over the last two decades. It draws attention to the relationships between changes in income and in other aspects of people's lives - not only in their jobs, earnings and benefits, but also in the households within which they live.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Income -- Great Britain; Income distribution -- Great Britain; Great Britain -- Economic conditions -- 1997-